Child’s Sundanese Story Dictation: A Case Study of A 5-Year-Old Indonesian Child - Mika Agesti; Winti Ananthia; Desiani N. Muliasari; Charlotte Ambat Harun; Endah Silawati (Early Childhood Research Journal (ECRJ), 2018)
This paper is a part of a bigger research about the implementation of story project that attempts to develop children’s critical literacy skill. The discussion in this paper focuses at the implementation of Sundanese story dictation on a 5-year-old child. The present study aims to identify the process of the story dictation, which is conducted for the very first time as a method to help children in expressing their own-created stories. Case study was employed as the research method. The subject of the present study was a 5-year-old boy who speaks Sundanese fluently and can express his ideas orally, in an kindergarten in Kabupaten Bandung. Story dictation was the method used to enable the subject to create a Sundanese story. The data were collected through video-tapped observation, in-depth interview and teacher’s field notes during the process of story dictation. Subsequently, the collected data were analysed. The finding revealed that the subject was able to complete the process of the story dictation voluntarily and could express his own story fluently. The investigation has shown that the created story can be categorised as a very good one.